Enhancing Law Enforcement Effectiveness Through Integrated Technological Innovations in Policing - Bagus Setiyono (Jurnal Scientia Indonesia, 2025)
Technological advancement has transformed contemporary law-enforcement practices, enabling police agencies to improve operational efficiency, decision-making processes, and public safety outcomes. This study examines the integration of multiple policing technologies—including digital reporting systems, body-worn cameras, crime-mapping tools, automated license plate recognition, and real-time communication platforms—within metropolitan police departments. Using a mixed-methods design, the research analyzes five years of operational performance data, evaluates changes in response-time metrics, and incorporates interviews with officers, analysts, and community representatives. Statistical analysis indicates that departments implementing integrated technology systems experience a 19% improvement in response efficiency, a 27% increase in investigative accuracy, and enhanced public transparency. Spatial analysis further demonstrates improved hotspot identification through geospatial tools, supporting optimized patrol deployment. However, the study also identifies challenges including uneven technological distribution, limited personnel training, and concerns related to data privacy. Ultimately, the findings highlight the transformative role of technology in strengthening policing capabilities while emphasizing the need for ethical governance frameworks. This study contributes to policing science by offering a comprehensive evaluation of how technological integration improves law-enforcement performance and proposing strategic recommendations for sustainable implementation.